Inductive logic programming : 27th International Conference, ILP 2017, Orléans, France, September 4-6, 2017, Revised selected papers /: 27th International Conference, ILP 2017, Orléans, France, September 4-6, 2017, Revised selected papers. (2018) - Unknown
No abstract available